Technology Enables Hr to Evolve to Business Execution: an Analysis: Exploring the Evolution of HRIS to Drive Business Success (Journal of Advances and Scholarly Researches in Allied Education, 2014)
A human resource information system (HRIS) isan information system or managed service that provides a single, centralizedview of the data that a human resource management (HRM)or human capital management (HCM) group requires forcompleting human resource (HR) processes. The objective of thisresearch is to trace the emergence of e-HRM (electronic- Human Resource Management)in the global arena as well as in the Indian scenario; to identify theunderlying factors and prerequisites for the success of an e-HRM venture; toidentify the challenges associated with the implementation and maintenance ofe-HRM systems and to offer recommendations and suggestions for enhancing theeffectiveness of e-HRM systems.